Cyberstalking: public danger, key factors and prevention - Kobets, Peter; Krasnova, Kristina (Przegląd Wschodnioeuropejski, 2019)
Cyberstalking has become a new form of crime and deviant behaviour. The authors research the problem of cyberstalking and intimidation via the Internet in details. These concepts are used interchangeably because all forms of stalking are threatening or have the purpose of distressing the victim (victim stress exhaustion). The authors tried to draw attention and show the interconnectcion between the social danger of cyberstalking and the violation of private life boundaries. The consequences of such interference can cause the significant harm to man interests, material harm; threaten the physical and mental health of a person. The authors in this article draw attention to the activities of people who use the Internet to threaten (intimidate) others. The phenomenon of cyberstalking constitutes one of the main aims of the analysis because it includes a rather large area of behavior performance (starting with the expression of threats to the theft of personal data). The main question of this research is simple: what makes an intelligent and law-abiding person in the offline world (outside the Internet), take part in anti-social or criminal activities online? The basic reason is the fact that the combination of technological and social factors encourages people to participate in crime or antisocial acts, such as incitement to violence against other people. The originality of the study is that the authors analyzed the public danger of cyberstalking and the consequences of privacy infringement by the negative impact on a person through the Internet. Authors highlight trends and developments, and give recommendations on how cyberstalking prevention matters can be improved.